Exposure to polycyclic aromatic hydrocarbons with special focus on cancer - Rengarajan, Thamaraiselvan; Rajendran, Peramaiyan; Nandakumar, Natarajan; Lokeshkumar, Boopathy; Rajendran, Palaniswami; Nishigaki, Ikuo (Elsevier, 2015)
Polycyclic aromatic hydrocarbons (PAHs) are a group of compounds consisting of two or more fused aromatic rings. Most of them are formed during incomplete combustion of organic materials such as wood and fossil fuels, petroleum products, and coal. The composition of PAH mixtures varies with the source and is also affected by selective weathering effects in the environment. PAHs are ubiquitous pollutants frequently found in a variety of environments such as fresh water and marine sediments, the atmosphere, and ice. Due to their widespread distribution, the environmental pollution due to PAHs has aroused global concern. Many PAHs and their epoxides are highly toxic, mutagenic and/or carcinogenic to microorganisms as well as to higher forms of life including humans. The main aim of this review is to provide contemporary information on PAH sources, route of exposure, worldwide emission rate, and adverse effects on humans, especially with reference to cancer.